2020
DOI: 10.3390/w12030694
|View full text |Cite
|
Sign up to set email alerts
|

Water Recharge of Jinan Karst Springs, Shandong, China

Abstract: As the main scavenge port of groundwater in the karst water system, most of the karst springs affected by human activities experienced discharge attenuation phenomenon in the north of China. Whilst artificial replenishment measures have been taken to keep water spewing, the results are not ideal in many karst springs. This is mainly because of poor understanding about the recharging water sources. This paper used the Jinan Spring region as an example to discuss about different spring water supply sources. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Type Ⅱ seemed to discharge both the flow component through the epikarst zone and the baseflow from the lower reservoir, as defined by Tritz et al (2011) who used two reservoirs (i.e., the upper epikarst/soil zone and the lower vadose and saturated zone) to simulate the behavior of a karst system catchment and assumed a fast flow through the epikarst and slow baseflow from the lower reservoir. The deep groundwater rising at springs was also observed by other researchers including Moore et al (2009), Bicalho et al (2012), Demiroglu (2016), Gil-Márquez et al (2019, Lorette et al (2018), andZhu et al (2020). Some implied fast transfer through conduits unlike Tritz et al (2011).…”
Section: Type ⅱ Springsupporting
confidence: 67%
See 3 more Smart Citations
“…Type Ⅱ seemed to discharge both the flow component through the epikarst zone and the baseflow from the lower reservoir, as defined by Tritz et al (2011) who used two reservoirs (i.e., the upper epikarst/soil zone and the lower vadose and saturated zone) to simulate the behavior of a karst system catchment and assumed a fast flow through the epikarst and slow baseflow from the lower reservoir. The deep groundwater rising at springs was also observed by other researchers including Moore et al (2009), Bicalho et al (2012), Demiroglu (2016), Gil-Márquez et al (2019, Lorette et al (2018), andZhu et al (2020). Some implied fast transfer through conduits unlike Tritz et al (2011).…”
Section: Type ⅱ Springsupporting
confidence: 67%
“…Given that springs in general originate along geologic contacts, faults, and ground depression (Fiorillo et al, 2018) and the layering of rocks relative to the slope of mountains affect both the number and discharge of springs in mountains (Mocior et al, 2015), the overturned strata (e.g., Cambro-Ordovician Yeongheung Formation (Oy) overlying Jurassic Bansong Formation (Jbs) along the thrust in Figure 1B) in this mountainous area can provide a pathway for deep groundwater upwelling as in Lorette et al (2018) who showed deep water rising at springs through the faulted anticline structure of Périgueux, France. Similarly, Zhu et al (2020) observed ascending springs along secondary tectonic fissures in the contact zone of limestone and magmatic rocks invaded as well as contact springs where the permeability of the local contact zone was enhanced. According to Zhu et al (2020), the two contact springs with relatively large and stable flow rates reflected the high proportion of karst water replenishment from the deep circulation.…”
Section: Geologymentioning
confidence: 75%
See 2 more Smart Citations
“…The data inversion of azimuthal EM LWD is usually conducted in real-time on the surface computer [10]. Therefore, the downhole data must be transmitted in real-time using remote transmission systems.…”
Section: Introductionmentioning
confidence: 99%